Factors Affecting the Level of Successful Land and Building Tax Revenue in Enrekang Regency - Risnawati. B (Income Journal Of Economics Development, 2022)
This study aims to determine what factors affect the success rate of Land and Building Tax receipts in Enrekang Regency. The research location is at the Bapenda Enrekang Regency office. The research time is approximately 2 months, namely in February - March 2021. The method in this research was using qualitative research methods. The results of this study are land and building tax revenues in Enrekang Regency are influenced by several factors, namely building area tax receipts, issuance of Tax Returns Payable (SPPT) and receipts from various types of land and building tax objects, where the building area and land tax objects and The building has a positive impact and an increase in tax revenue because if the amount or amount increases, the amount of incoming taxes will also be even greater while the Tax Returns Payable (SPPT) which tends to increase will have a negative impact or decrease in Enrekang Regency tax revenues. Tax revenue was very influential on the regional income of Enrekang Regency and this revenue was also influenced by the accuracy of the community in carrying out their obligations in paying taxes.